Nonequilibrium thermodynamics approach to the mesomechanics of a deformed solid as a multiscale system; Procedia Engineering; Vol. 1, iss. 1 - Panin V. E. Viktor Evgenyevich (2009, 2009)
Based on non-equilibrium thermodynamics, we develop a methodology of describing a deformed solid as a multiscale system. It is concluded that all mechanisms of plastic deformation and fracture of solids as local structural transformations in the zones of stress concentrators of different scales are common in nature. All types of strain-induced defects are generated in hydrostatic tension zones near stress concentrators, where the local non-equilibrium thermodynamic Gibbs potential should be considered. The corpuscular-wave dualism of plastic shear is demonstrated and its specific character at different structural scale levels of plastic deformation is shown